2015
DOI: 10.1590/1983-40632015v4537687
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of water-crop production models for ratoon sugarcane

Abstract: Production models need to be tested at different locations to be used as an agricultural planning tool. Hydric relations and performances of water-crop production models were used to estimate ratoon sugarcane yield along nine production cycles, in Paranavaí, Paraná State, Brazil. The crop reference and real evapotranspiration, soil water storage, water deficit and surplus were evaluated. The "Stewart" and "Jensen" models showed the best performance to estimate ratoon sugarcane yield. Water availability in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In a study on sugar cane in Brazil, the λ coefficient was calculated for germination to tillering, development and growth reduction (sucrose accumulation). The λ coefficient at the growth stage mentioned was estimated to be 0.43, 0.39 and 0.07, respectively (Souza et al, 2015). The results of the study mentioned showed that sugar cane sensitivity in the germination to the tillering stage was greater than that in other growth stages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on sugar cane in Brazil, the λ coefficient was calculated for germination to tillering, development and growth reduction (sucrose accumulation). The λ coefficient at the growth stage mentioned was estimated to be 0.43, 0.39 and 0.07, respectively (Souza et al, 2015). The results of the study mentioned showed that sugar cane sensitivity in the germination to the tillering stage was greater than that in other growth stages.…”
Section: Resultsmentioning
confidence: 99%
“…The mentioned models provide good estimations of crop yield, and they optimize irrigation water management during the growing season (Chen et al, 2014). Water stress sensitivity coefficients in the Jensen model were estimated for maize growth stages in Belgium (Kipkorir & Raes, 2002), sorghum in the United States (Jensen, 1968) and sugar cane in Brazil (Souza et al, 2015).…”
mentioning
confidence: 99%
“…Doorenbos and Kassam (1994), in which all water, nutritional and phytosanitary needs are addressed. The potential productivity penalization as a function of water deficit was performed using Jensen equation (Jensen, 1968;Souza et al, 2013;Souza et al, 2015):…”
Section: Methodsmentioning
confidence: 99%
“…In general, the soil of the experimental area cultivated with sugarcane showed low water availability for plants in the layers analyzed (Table 6), which is characteristic of soils with low clay contents [5,37]. There was no statistical difference between the layers (p > 0.05), but the highest AWC 1 and EAW 1 occur in the soil layers at 0.2 to 0.4 m and 0.4 to 0.6 m depth due to the higher amount of clay and microporosity [5].…”
Section: Water Availabilitymentioning
confidence: 99%